Robotic and laparoscopic liver surgery for colorectal liver metastases: an experience from a German Academic Center - Rahimli, Mirhasan; Perrakis, Aristotelis; Schellerer, Vera; Gumbs, Andrew; Lorenz, Eric; Franz, Mareike; Arend, Joerg; Negrini, Victor-Radu; Croner, Roland Siegfried (World Journal of Surgical Oncology, 2020)
Background Minimally invasive liver surgery (MILS) in the treatment of colorectal liver metastases (CRLM) is increasing in incidence. The aim of this work was to present our experience by reporting short-term and long-term outcomes after MILS for CRLM with comparative analysis of laparoscopic (LLS) and robotic liver surgery (RLS). Methods Twenty-five patients with CRLM, who underwent MILS between May 2012 and March 2020, were selected from our retrospective registry of minimally invasive liver surgery (MD-MILS). Thirteen of these patients underwent LLS and 12 RLS. Short-term and long-term outcomes of both groups were analyzed. Results Operating time was significantly longer in the RLS vs. the LLS group (342.0 vs. 200.0 min; p = 0.004). There was no significant difference between the laparoscopic vs. the robotic group regarding length of postoperative stay (8.8 days), measured blood loss (430.4 ml), intraoperative blood transfusion, overall morbidity (20.0%), and liver surgery related morbidity (4%). The mean BMI was 27.3 (range from 19.2 to 44.8) kg/m(2). The 30-day mortality was 0%. R0 resection was achieved in all patients (100.0%) in RLS vs. 10 patients (76.9%) in LLS. Major resections were carried out in 32.0% of the cases, and 84.0% of the patients showed intra-abdominal adhesions due to previous abdominal surgery. In 24.0% of cases, the tumor was bilobar, the maximum number of tumors removed was 9, and the largest tumor was 8.5 cm in diameter. The 1-, 3- and 5-year overall survival rates were 84, 56.9, and 48.7%, respectively. The 1- and 3-year overall recurrence-free survival rates were 49.6 and 36.2%, respectively, without significant differences between RLS vs. LLS. Conclusion Minimally invasive liver surgery for CRLM is safe and feasible. Minimally invasive resection of multiple lesions and large tumors is also possible. RLS may help to achieve higher rates of R0 resections. High BMI, previous abdominal surgery, and bilobar tumors are not a barrier for MILS. Laparoscopic and robotic liver resections for CRLM provide similar long-term results which are comparable to open techniques.
CRIS-Team WoS Importer:2021-01-08